Adductor Muscle Injuries in UEFA Soccer Athletes: A Matched-Cohort Analysis of Injury Rate, Return to Play, and Player Performance From 2000 to 2015. Issue 9 (23rd September 2021) - Lavoie-Gagne, Ophelie; Mehta, Nabil; Patel, Sumit; Cohn, Matthew R.; Forlenza, Enrico; Nwachukwu, Benedict U.; Forsythe, Brian
Background: The effects of adductor muscle injury on performance in soccer athletes are unknown. Purpose: To (1) determine the rate and time to return to play (RTP) after adductor muscle injury, (2) investigate the rate of reinjury after RTP, and (3) investigate any long-term effects of injury on elite soccer player performance. Study Design: Cohort study; Level of evidence, 3. Methods: Using publicly available records, athletes sustaining adductor muscle injury were identified across the 5 major European soccer leagues (English Premier League, Bundesliga, La Liga, Ligue 1, and Serie A) between 2000 and 2015. Injured athletes were matched to controls by demographic characteristics and performance metrics from 1 season before the index timepoint. Investigations included the rate of RTP, reinjuries, player characteristics associated with RTP within 2 seasons, player availability, field time, and performance metrics during the 4 seasons after injury. Results: A total of 671 players with adductor muscle injury were included. Based on time to RTP, 86% of injuries were mild to moderate (4-28 days missed), and 4% required surgical intervention. Players with adductor muscle injury were absent for a median of 22 days (range, 1-700 days) and 4 games (range, 1-76 games). A total of 521 (78%) players returned at the same level, with no demographic or clinical characteristics associated with RTP on the multivariable regression. Of those returning to play, 143 (21%) experienced adductor reinjury. After RTP, defenders demonstrated decreased field time compared with controls ( P < .05). As compared with controls, defenders and midfielders scored more points and goals per game during the season of the injury ( P < .01), while attackers recorded more goals and assists per game the season after injury ( P < .05). Conclusion: Only 3 in 4 players (78%) returned to participate in an official match, and the reinjury rate was high (21%). After RTP, defenders demonstrated decreased field time versus controls. On the other hand, defenders and midfielders recorded more points and goals per game, while attackers recorded more goals and assists per game versus controls. Although the multivariable analysis results did not identify player characteristics associated with RTP, there was a position-dependent association on player performance after RTP.